Understanding the role of research in the evolution of fertilizer policies in Malawi - Johnson, Michael E.; Birner, Regina (International Food Policy Research Institute, 2013)
This study examines the role of research in agricultural policy making in Malawi at a time when the Africa Union and the New Partnership for Africa’s Development have been seeking to promote greater evidenced-based decision making in agriculture. Drawing on both theory and actual past experiences documented in the literature, results are intended to improve our understanding of the extent to which research has played any role in influencing policy change in Malawi. This is done in the context of the evolution of the country’s fertilizer subsidy policies.